AGN outflows as neutrino sources: an observational test. Issue 3 (6th April 2018) - Padovani, P; Turcati, A; Resconi, E
Abstract: We test the recently proposed idea that outflows associated with Active Galactic Nuclei (AGN) could be neutrino emitters in two complementary ways. First, we cross-correlate a list of 94 'bona fide' AGN outflows with the most complete and updated repository of IceCube neutrinos currently publicly available, assembled by us for this purpose. It turns out that AGN with outflows matched to an IceCube neutrino have outflow and kinetic energy rates, and bolometric powers larger than those of AGN with outflows not matched to neutrinos. Secondly, we carry out a statistical analysis on a catalogue of [O iii ] λ5007 line profiles using a sample of 23 264 AGN at z < 0.4, a subsample of which includes mostly possible outflow sources. We find no significant evidence of an association between the AGN and the IceCube events, although we get the smallest p -values (∼6 and 18 per cent, respectively, pre-trial) for relatively high velocities and luminosities. Our results are consistent with a scenario where AGN outflows are neutrino emitters but at present do not provide a significant signal. This can be tested with better statistics and source stacking. A predominant role of AGN outflows in explaining the IceCube data appears in any case to be ruled out.